Increasing Corporate Competitive Advantages in Customer Loyalty Using Electronic Applications Laundry - Faisal Faisal (Journal of Applied Sciences and Advanced Technology, 2019)
The business application solutions in an electronic form based on information communication technology is the company's commitment to enhancing the competitive advantage of its corporate customers in terms of efficiency, effectiveness, performance, and business development. The research objective to provide laundry services to customers in implementing laundry application services in electronic form, so that it is expected to simplify and accelerate work and improve the company's competitive advantage. This research uses descriptive analytic and design methods by presenting a summary of interviews and field surveys, model diagrams and navigation structures in developing laundry service applications. The research output is to be able to perform the design process and empower the electronic model of laundry service, this research is also expected to increase the competitive advantage of corporate customers.